1986
DOI: 10.1037/0278-6133.5.2.125
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biochemical validation of self-reported cigarette smoking on treatment success and on misreporting abstinence.

Abstract: Many investigators have reported that cigarette smokers who are trying to quit often falsely report being abstinent at the end of treatment. Unfortunately, much of the previous research designed to investigate this problem has been flawed, making the results difficult to interpret. We attempted to avoid these flaws and to investigate the measurement of alveolar carbon monoxide (CO) levels to validate self-reported smoking rates at the end of treatment. Participants in behavioral cessation clinics were randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…17 One would eXpWct in our data that despite a self-report bias toward claiming smoking cessation from within a cessation intervention program, there should also be an opposed bias in the case of carbon monoxide measurement toward looking honest in the eyes of the clinic interviewer, in whose presence the results are obtained. We found that, consistentwith this interpretation, thebias evident when cotinine was used as the biochemical marker was signifcantly greater than when carbon monoxide was used.…”
Section: Disussionmentioning
confidence: 99%
“…17 One would eXpWct in our data that despite a self-report bias toward claiming smoking cessation from within a cessation intervention program, there should also be an opposed bias in the case of carbon monoxide measurement toward looking honest in the eyes of the clinic interviewer, in whose presence the results are obtained. We found that, consistentwith this interpretation, thebias evident when cotinine was used as the biochemical marker was signifcantly greater than when carbon monoxide was used.…”
Section: Disussionmentioning
confidence: 99%
“…The use of self-report rather than objective measures (including biochemical measures and hospital records) is another limitation of the study. Studies comparing self-report and biochemical measures of tobacco use have found misclassification rates (percentage of smokers or other tobacco users who say they quit who have biochemical evidence of continued tobacco use) of about 5%-16%, depending on the population studied (e.g., Atterbring et al, 2001;Glynn, Gruder, & Jergerski, 1986;Miller et al, 1997). The method of measurement for tobacco use cessation is an important issue for health care facilities wishing to set performance goals.…”
Section: Discussionmentioning
confidence: 97%
“…Past studies have indicated that asking participants to provide saliva samples for validation increases the number of accurate self-reported quitting statuses received (Glynn et al, 1986).…”
Section: Recruitment and Registration Of Subjectsmentioning
confidence: 99%